Socio-Psychological Predictors of Suicidal Ideation among Young Adults in Oyo State, Nigeria - Adeyemo, David. A; Olunloyo, B.O; Agokei, Stanley Peter (Utan Kayu Publishing, 2024)
This study examined the socio-psychological predictors of suicidal ideation among young adults in Oyo state. Simple random sampling technique was employed in the selection of 288 young adults between 20 and 40 years. Participants responded to standardized self-report measures regarding bio-demographic data, emotional intelligence, self-esteem, social support, anxiety, depression, social economic status and suicidal ideation. Descriptive statistics, Pearson Product Moment Correlation and multiple regression analysis were used to analyze the data. The result demonstrated that emotional intelligence, self-esteem, social support and socio-economic status had significant negative relationship with suicidal ideation. However, anxiety and depression had significant positive relationship with the criterion measure. The relationship between gender and the criterion measure was not significant. The independent variables accounted for 39.8% of the variance of suicidal ideation. On the basis of the findings, it is suggested that psychological interventions can be applied in reducing suicidal ideation.